Implementing a breathing technique to manage performance anxiety in softball - Garza, L.; Ford, S. J. (The Sport Journal, 2009)
An intervention strategy was developed, implemented, and evaluated that aimed at minimizing performance anxiety. The goal was to guide NCAA Division I softball athletes in using a breathing technique that, by contributing to the management of performance anxiety, would help each athlete reach full potential on the softball field. The strategy focused on the effects of the breathing technique on the participants` heart rates, in relation to daily anxiety events; a heart rate monitor and anxiety logs were used to obtain data. All 4 of the athletes studied indicated improvement at various stages in the program.